Climate change implications of shifting forest management strategy in a boreal forest ecosystem of Norway. (26th November 2013) - Bright, Ryan M.; Antón‐Fernández, Clara; Astrup, Rasmus; Cherubini, Francesco; Kvalevåg, Maria; Strømman, Anders H.
Abstract Empirical models alongside remotely sensed and station measured meteorological observations are employed to investigate both the local and global direct climate change impacts of alternative forest management strategies within a boreal ecosystem of eastern Norway. Stand‐level analysis is firstly executed to attribute differences in daily, seasonal, and annual mean surface temperatures to differences in surface intrinsic biophysical properties across conifer, deciduous, and clear‐cut sites. Relative to a conifer site, a slight local cooling of −0.13 °C at a deciduous site and −0.25 °C at a clear‐cut site were observed over a 6‐year period, which were mostly attributed to a higher albedo throughout the year. When monthly mean albedo trajectories over the entire managed forest landscape were taken into consideration, we found that strategies promoting natural regeneration of coniferous sites with native deciduous species led to substantial global direct climate cooling benefits relative to those maintaining current silviculture regimes – despite predicted long‐term regional warming feedbacks and a reduced albedo in spring and autumn months. The magnitude and duration of the cooling benefit depended largely on whether management strategies jointly promoted an enhanced material supply over business‐as‐usual levels. Expressed in terms of an equivalent CO2 emission pulse at the start of the simulation, the net climate response at the end of the 21st century spanned −8 to −159 Tg‐CO2‐eq., depending on whether near‐term harvest levels increased or followed current trends, respectively. This magnitude equates to approximately −20 to −300% of Norway's annual domestic (production) emission impact. Our analysis supports the assertion that a carbon‐only focus in the design and implementation of forest management policy in boreal and other climatically similar regions can be counterproductive – and at best – suboptimal if boreal forests are to be used as a tool to mitigate global warming.